Percutaneous Left Appendage Closure with the Watchman Device; The Challenges Lie Ahead: A Narrative Mini Review - Mohammad Hasan Namazi; Isa Khaheshi; Elham Barkhordari; Mohammadreza Naderian; Farbod Zahedi Tajrishi (Journal of Clinical and Diagnostic Research, 2018)
Atrial Fibrillation (AF) is the most prevalent arrhythmia occurring especially in the elderly. The extremely dire complication of this condition is cardiac thromboembolism that commonly arises from the Left Atrial Appendage (LAA) and may lead to stroke. Currently, guidelines recommend Oral Anticoagulants (OACs) as the therapy of choice for AF patients who are considered susceptible to develop stroke. Although, OACs have been proven effective for this purpose, they are not always an appropriate choice as they increase the likelihood of major bleeding, which can be specifically problematic to patients who for any reason, already have a moderate to high risk for bleeding. Moreover, the need for frequent PT, PTT and INR assessments and patients’ non-compliance can add to the problems of long-term use of OACs. The search for alternative treatment choices has resulted in the evolution of Percutaneous Left Atrial Appendage Closure (LAAC). Multiple devices have been developed to be applied to this method, the most well-studied of which is the Watchman device. At the moment, percutaneous LAAC is being recommended only by European guidelines and just for patients with non-valvular AF (NVAF) who have a high potential for stroke and who are contraindicated to OAC therapy. The method still offers several challenges and requires more evidence to be approved as a definitive treatment option. In this article, we reviewed the concept behind LAAC and its indications, the available evidence on safety and effectiveness of LAAC with Watchman and focused on the challenges underlying this developing therapy.